2021
DOI: 10.3389/fneur.2021.706166
|View full text |Cite
|
Sign up to set email alerts
|

Treating Aggression and Self-destructive Behaviors by Stimulating the Nucleus Accumbens: A Case Series

Abstract: Self-destructive and aggressive behaviors can have a significant impact on the quality of life of affected individuals and their carrers. While deep brain stimulation (DBS) has been applied to the treatment of self-destructive and aggressive behaviors in isolated cases, clinical data on this treatment modality are still lacking. We therefore assessed responses to treatment with bilateral DBS of the nucleus accumbens in six patients with severe self-destructive and aggressive behaviors. Three patients had Toure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…There are several studies on the role of DBS in aggressive behavior, which have targeted the posterior hypothalamic region. However, clinical data on this treatment modality are still lacking 24 ; especially, in pediatric populations where evidence is advancing slowly. 25 Therefore, we conducted a follow-up study in…”
mentioning
confidence: 99%
“…There are several studies on the role of DBS in aggressive behavior, which have targeted the posterior hypothalamic region. However, clinical data on this treatment modality are still lacking 24 ; especially, in pediatric populations where evidence is advancing slowly. 25 Therefore, we conducted a follow-up study in…”
mentioning
confidence: 99%
“…Moreover, antagonism of both dopamine receptor types 1 and 2 in the nAcc have been described as reducing the rewarding value of aggressive behaviors ( 52 54 ). In line with these findings, two case reports ( 55 , 56 ) and one case series ( 57 ) reporting on patients treated with deep brain stimulation of the nAcc for severe refractory aggressive behaviors, have shown long lasting positive results ( 58 ).…”
Section: Introductionmentioning
confidence: 60%
“…Except for 1 study (32), no surgical parameters were determined. In 47.06% of the publications (6, 12, 21-25, 35), the brain target was the posteromedial hypothalamic nuclei (pHypN), a well-known target; while other groups proposed earlier targets (5,34) or ventral regions (27,(29)(30)(31)33) or a combination of short-subcortical brain regions (28, 32, 34). Similarly, in most studies, the technique and electrode implantation coordinates were reported, although, in 4 articles, they were not reported (28, [31][32][33].…”
Section: Neurosurgical Parametersmentioning
confidence: 99%
“…Voltage intensity ranged between 0.5V and 6.5V, frequency between 15 and 185 Hz, and pulse width between 60 and 360µs. In 3 studiesthis information was not recorded (22,28,30). Clinical outcomes, effectiveness, and complications.…”
Section: Neurosurgical Parametersmentioning
confidence: 99%
See 1 more Smart Citation